The specificity of employment forms in Poland in the context of implementing the Directive on improving working conditions in platform work: Analysis of regulatory challenges and adaptive potential - Krawczyński, Kacper; Walczak, Tomasz (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The article examines the specific forms of employment in Poland in the context of the implementation of Directive 2024/1689, which aims to improve working conditions on digital platforms. The rise of platform work has transformed traditional employment models, offering flexibility while simultaneously raising regulatory challenges related to worker protection and employment stability. The main part of the text focuses on the structure of the Polish labor market, with particular emphasis on civil law contracts and self-employment in platform-based work. Special attention is given to the presumption of an employment relationship, which may affect market competitiveness and the adaptation of labor law to EU requirements. Key legislative challenges and potential regulatory approaches are discussed, aiming to balance social protection with labor market flexibility. Excessive regulatory intervention may limit the development of platform work; therefore, a balanced model is needed to ensure fair working conditions while supporting the continued growth of the digital economy.